FLOOD RISK FOR RESIDENCE = HAZARD X CONSEQUENCE: THE PARAMETERS INVOLVED. - Anthony, Peter & Adepoju, Adetoye Sulaiman (International Journal of Research Science and Management, 2018)
Evidently, the world has experienced devastating floods which affected millions of people and caused untold hardship to the affected population. Flooding is one of the leading devastating hazards worldwide. The most vulnerable population are the poor who are the majority in most human settlements. Social perception in risk taken play a crucial role, which could lead to adverse or positive outcomes in risk conditions. The risk involved in flood occurrence affects human properties, social, geological and economic systems, in extreme cases it results to loss of lives. Hazard parameters which could be measured to quantify direct flood hazards are majorly volume, depth, volumetric flow rate, velocity, temperature, density and salinity. Increase in flood losses are the aftermath of risk taken. The research aims at creating more awareness regarding flood risk with emphasis on the consequence and the parameters to be considered. To realize this data was collected from books, journals and internet. The finding revealed that there is need to minimize taken risk so as to reduce loses of lives and properties especially in flood prone areas.